Synthesis and Biological Screening of Pyrano[2,3-b]quinoline Derivatives - Abirami, M.; Thamarai Selvi, S.; Nadaraj, V.; Daniel Thangadurai, T. (Asian Journal of Chemistry, 2021)
Herein, a novel ionic liquid catalyzed synthesis of 3-acetylpyrano[2,3-b]quinolin-2(1H)-ones (3a-e) from substituted 3-formylquinolin-2(1H)-ones (1a-e) and ethyl acetoacetate (2) through Knoevenagel condensation is reported. We have perceived the application of microwave irradiation and ionic liquid for carrying out pollution free and ecofriendly chemical reactions. These reactions proceeded much faster in ionic liquid medium under microwave irradiation. The structures of quinoline derivatives (3a-e) were characterized by standard physico-chemical techniques. The synthesized quinoline derivatives (3a-e) were also evaluated for their in vitro antimicrobial screening on different strains of bacteria and fungi.